Traditional and positive mental maps for Latin American leadership: Adapting Quinn’s model to the Latin American context - MCCLELLAN, Jeffrey (Estudios de Administración, 2023)
As external models of leadership — commonly used in Latin America — are not always culturally relevant to the region, this article explores how Robert Quinn’s (2015) traditional and positive mental maps for organizational leadership can be adapted for use in the Latin American context. Quinn’s model is outlined and discussed and is followed by an exploration of the cultural differences between the U.S. and Latin America that would require adaptation The author then reviews the research on traditional and alternative approaches to leadership in Latin America and proposes alternative mental maps for the region.